Development of Tinnitus and Hyperacusis in a Mouse Model of Tobramycin Cochleotoxicity - Longenecker, Ryan J.; Gu, Rende; Homan, Jennifer; Kil, Jonathan (Frontiers in Molecular Neuroscience, 2021)
Aminoglycosides (AG) antibiotics are a common treatment for recurrent infections in cystic fibrosis (CF) patients. AGs are highly ototoxic, resulting in a range of auditory dysfunctions. It was recently shown that the acoustic startle reflex (ASR) can assess behavioral evidence of hyperacusis and tinnitus in an amikacin cochleotoxicity mouse model. The goal of this study was to establish if tobramycin treatment led to similar changes in ASR behavior and to establish whether ebselen can prevent the development of these maladaptive neuroplastic symptoms. CBA/Ca mice were divided into three groups: Group 1 served as a control and did not receive tobramycin or ebselen, Group 2 received tobramycin (200 mg/kg/s.c.) and the vehicle (DMSO/saline/i.p.) daily for 14 continuous days, and Group 3 received the same dose/schedule of tobramycin as Group 2 and ebselen at (20 mg/kg/i.p.). Auditory brainstem response (ABR) and ASR hearing assessments were collected at baseline and 2, 6, 10, 14, and 18 weeks from the start of treatment. ASR tests included input/output (I/O) functions which assess general hearing and hyperacusis, and Gap-induced prepulse inhibition of the acoustic startle (GPIAS) to assess tinnitus. At 18 weeks, histologic analysis showed predominantly normal appearing hair cells and spiral ganglion neuron (SGN) synapses. Following 14 days of tobramycin injections, 16 kHz thresholds increased from baseline and fluctuated over the 18-week recovery period. I/O functions revealed exaggerated startle response magnitudes in 50% of mice over the same period. Gap detection deficits, representing behavioral evidence of tinnitus, were observed in a smaller subset (36%) of animals. Interestingly, increases in ABR wave III/wave I amplitude ratios were observed. These tobramycin data corroborate previous findings that AGs can result in hearing dysfunctions. We show that a 14-day course of tobramycin treatment can cause similar levels of hearing loss and tinnitus, when compared to a 14-day course of amikacin, but less hyperacusis. Evidence suggests that tinnitus and hyperacusis might be common side effects of AG antibiotics.